Performance Information Use under Financial Stress: How Do Public, Nonprofit, and Private Organizations Differ?. Issue 1 (2nd January 2021) - Pfiffner, Roger; Ritz, Adrian; Brewer, Gene A.
Abstract: Performance management is becoming increasingly important in long-term health care because of rising quality standards and scarce resources. The ongoing Coronavirus pandemic illustrates the dynamic nature of emerging events in the health sector and underscores the importance of managing for results in suboptimal conditions. This study investigates whether managers in public, nonprofit, and private sector nursing homes differ in how they use performance information when their organizations are under severe financial stress. Based on the survey and archival data for 579 organizations in Switzerland, this study reveals substantial cross-sector differences in the use of performance information for managing efficiency and service quality. Our key findings suggest that managers in all three sectors utilize performance information differently when under financial stress. While financial stress hampers managers' use of performance information for managing efficiency in the public sector, it fosters greater use in the nonprofit and private sectors, with the latter being even more responsive. Nonprofit organizations give more attention to preserving the quality of care, apparently fearing that increased emphasis on efficiency could undercut quality. The implications for theory and practice are discussed.